Meta-Analysis: Impact of Just-in-Time Implementation on Cost Efficiency and Profits - Urohman, Taufiq; Suryana, Alvian Jihad; Pandin, Maria Yovita R.; Riyadi, Slamet (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Excess inventory results in losses for the industry due to capital being held back, increased storage costs, incurring costs for taxes and inventory insurance, the risk of falling prices and quality, and the potential for damage and theft. Inventory shortages can also cause losses because they can disrupt the production process. This research identified and analyzed 20 journals related to the implementation and impact of just-in-time implementation. Implementing just in time can reduce inventory costs, increase time efficiency and production costs so that producers can focus more on quality, and increase company profits. The implementation of just-in-time is accompanied by an increase in other higher costs, this could be due to constraints in the supply chain, and the risk of erratic demand.